Formation of Professional and Labor Competence of Schoolchildren With Intellectual Disorders by Means of Professional Orientation - Bakhmat, Nataliia; Verzhihovska, Olena (Pedagogical Discourse, 2020)
In the article process of vocational guidance as criterion of overall performance of staff of special schools for children with psychophysical violations, and also as an important condition and means for formation of professional and labor competence of pupils is considered. The short interval of time which is taken away for labor training forces special school to unite the general labor preparation in primary classes with vocational training which begins in the senior classes. Features of intellectual development, the available violations of physical development of pupils of special schools, don’t allow the pupil to choose independently the profession owing to not ability to define requirements of the profession to the candidate, lack of ability to estimate critically the abilities, to correlate them with required professions, to execute monitoring of the profession in labor market. These problems have to be solved in the course of vocational guidance at special school which includes such stages of work as professional education, professional promotion, professional consultation, professional diagnostics, professional selection by the exception improper to the professions of the pupil. The scientific research of the author conducted in some cities of Ukraine showed that professional orientation work at special schools is carried out formally, limited to not numerous classes in labor training, registration of stands on which information for pupils and their parents about professional schools or lyceums of the city is placed. Questioning of graduates of special schools, conversations with their parents, studying of school documentation allowed to draw the conclusion that most of pupils after leaving school experience considerable difficulties at employment, further vocational education. The results of the research showed that 14% of total number of the surveyed increased the vocational training at schools, and work at a factory by the received profession. 22 % of respondents were employed as general workers, that is not in the specialty, other graduates of schools remained not employed. One of the reasons of such situation is in underestimation of its role by heads of special educational institutions.